Service design applications into new service development process : The case of Finnish start-ups - Tran, Huy (My University, 2020)
Global economy has witnessed a great contribution from service sector, which accounted for 68.9% of the world GDP in 2015 (World Bank, 2017). The importance of service sector has been accelerated thanks to the growth of the Internet and digitalization globally. As a consequence, the competition to win the most portion in the service pie gets tougher, especially for newcomers. Indeed, start-up companies confront a high rate of failure (Patel, 2015). In order to keep up with the competition, service innovation is considered as a key, in which service design emerges as an innovative approach with concrete process, tools and methods involving different stakeholders into developing new services. However, there are a limited number of studies investigating the linkage between service design and new service development (Papastathopoulou & Hultink, 2012; Clatworthy, 2013; Yu & Sangiorgi, 2014). The study aims to answer the research question how service design can be applied into new service development process by first investigating the current literature. Accordingly, a qualitative research was conducted to collect data so that the analysis and new findings are supported. Four start-up companies from different business lines, including sport and leisure, transport and logistics, e-commerce, and food and beverage, had participated in the semi-structured interviews. The thesis findings implement the idea of Clatworhty (2013), and Yu and Sangiorgi (2014), who state that service design is a narrow phase being focused mainly within the front-end planning. The association between service design and new service development process has been pointed out clearly from the case studies, contributing a significant empirical study to the current literature. In addition, the study reinforces the essential role of service design tools and methods, and stakeholders along new service development process.
Keywords: Service Design, Start-up, New Service Development, Service Innovation